Depression among pregnant teenagers receiving antenatal care from primary healthcare facilities in Mbarara city, Southwestern Uganda - Moses Muwanguzi; Sarah Oworinawe; Derrick Mwahuzi; Pavey Lila; Scholastic Ashaba (BMC Pregnancy and Childbirth, 2025)
Background: Depression is a serious mental health condition whose risk is highest among women during pregnancy. The risk is high among pregnant teenagers due to intertwined developmental, hormone-mediated physical and psychosocial changes of pregnancy, with significant negative impacts on the unborn baby and the mother. This study aimed to determine the prevalence of depression and associated factors among pregnant teenagers in Mbarara city, southwestern Uganda. Methods: This was a cross-sectional study where we enrolled pregnant teenagers (13–19 years) attending antenatal care at 4 selected lower healthcare facilities in Mbarara City southwestern Uganda. We collected information on depression, resilience, social support and household food insecurity. Depression was defined as a score>10on the Edinburgh Postnatal Depression Scale (EPDS). Resilience was assessed using the 14-item Wagnild and Young Resilience Scale, Multi-dimensional Scale of perceived social support (MDSPSS) assessed perceived social support, and Household Food Insecurity Access Scale (HFIAS) assessed food insecurity in addition to sociodemographic variables. We run logistic regression analysis to determine factors associated with depression. Results: A total of 373 participants were recruited; median age was 19 (IQR: 18–19) years, 59% attained primary level education. The prevalence of depression was 35.9% (95% CI: 31.1% to 41.0%). Factors significantly associated with depression were current alcohol use (aOR=1.98, 95% CI: 1.18 – 3.32, p=0.010), and food insecurity (aOR=2.24, 95% CI: 1.25 – 4.01, p=0.006). Factors that reduced the odds of depression included resilience (aOR=0.93, 95% CI: 0.91 – 0.97, p=0.001) and family social support (aOR=0.94, 95% CI: 0.88 – 0.99, p=0.031). Conclusions and recommendations: In this study the prevalence of depression among pregnant teenagers was significantly high. Mental health services should be integrated in the antenatal care clinics to address the mental health needs of pregnant teenagers. We recommend further studies to explore the lived experiences focusing on the challenges and further understanding of their coping strategies and other possible confounders of depression. In addition, longitudinal studies should be conducted to establish the temporal relationships between the different factors related to depression to support intervention studies that promote the mental health of young mothers.
Keywords: Depression; Pregnant teenagers; Resilience; Alcohol use; Food insecurity; Social support; Uganda